Computer simulation of the steady state currents at enzyme doped carbon paste electrodes - Ivanauskas, Feliksas; Laurinavičius, Valdas; Šimkus, Remigijus; Kaunietis, Irmantas (Lietuvos matematikos rinkinys, 2005)
Reaction-diffusion in porous enzyme-doped carbon paste electrode has been analyzed. The plate-gap model of such electrode has been proposed. The steady state current was calculated for the wide range of given parameters. The apparent parameters (apparent maximal currents and apparent Michaelis constants) of the modelled electrode were calculated. Relationships between apparent and given parameters were derived.
Keywords: reaction-diffusion; modelling; amperometric biosensors; porous electrode